COMBINING AHP METHODS WITH BOCR TO DETERMINE THE FEASIBILITY OF TRAININGS TO ENTREPRENEURS THROUGH MFIS IN PAKISTAN - Abro, Paras; Bhutto, Dr. Arabella; Pitafi, Dr. Adnan; Katper, Sheeraz Akhter (The journal of contemporary issues in business and government, 2021)
The aim of the study is to explore the microfinance industry in Pakistan and their credit plus approach targeting entrepreneurship development in particular and aims to yield insights into the Benefits, Costs, Opportunities and risks of the provision of trainings through FMIs in Pakistan. The study evaluates and determines the alternative possibilities of providing training to the clients’ particularity enterprise loan borrowers of three leading micro finance institution in Pakistan. Micro-credit and trainings jointly contribute positively to SMEs growth and Entrepreneurship trainings may also help micro business entrepreneurs use microfinance more effectively. Pakistan has a sound microfinance structure but its outreach seems to be much lower than other peer nations in the world. On the basis of the criteria, the approach proposes to utilise BOCR (benefit, opportunity, cost, and risk) paradigm trainings in conjunction with the analytic hierarchy process (AHP) to find qualities that must describe an alternative of providing direct or indirect trainings through MIFs. Qualitative approach was used for this study and exploratory in nature. Semi-structured questionnaire was used in-depth interviews for the data collection. The results identified certain benefits, costs, risks and opportunities associated with the trainings for the selection of one of the alternative. The AHP model is prepared showing all the criteria and alternatives to be pair wise tests and analysis in the second step of the research in future.